Faktor-Faktor Terjadinya Gelandangan Dan Pengemis Di Kota Manado - Waleleng, Grace J.; Pratiknjo, Maria (AGRI-SOSIOEKONOMI, 2023)
This research intends to find the factors that cause homeless people and beggars in the city of Manado. The research was conducted for 6 (six) months, from July to December 2022. The research location is in Manado City. Using a qualitative research method with an analytical descriptive approach This research was conducted by collecting various data, namely observation, in-depth interviews, and document studies. The results of the study found that the factors causing the occurrence of homeless people and beggars in Manado City were: Poverty, Economic Factors, Physical Limitations and Mental Disorders, Freedom and Enjoyment of Homeless Life, Socio-Cultural Factors, Education and Skills Limitations, Population Problems, Frustration Due to Family and Household Problems, and Age Factors. The public impact if the problems of homeless people and beggars (beggars) are not addressed, namely Disturbing Public Order, Disturbing the Cleanliness and Beauty of the City, Disturbing Comfort, Disturbing Security and Order, Population Problems, and Causing Crime. It is hoped that there will be empowerment, construction of "social solidarity villages", affirmation of sanctions, and cross-sectoral cooperation in dealing with beggars in Manado City.